Clients' experiences of treatment and recovery in borderline personality disorder: A meta-synthesis of qualitative studies. (2nd November 2018) - Katsakou, Christina; Pistrang, Nancy
Abstract: Objective: This review synthesized findings from qualitative studies exploring clients' experiences of their treatment for borderline personality disorder (BPD) and their perceptions of recovery.Method: Fourteen studies were identified through searches in three electronic databases. The Critical Appraisal Skills Programme was used to appraise the methodological quality of the studies. Thematic analysis was used to synthesize the findings.Results: The meta-synthesis identified 10 themes, grouped into 3 domains. The first domain, "Areas of change, " suggests that clients make changes in four main areas: developing self-acceptance and self-confidence; controlling difficult thoughts and emotions; practising new ways of relating to others; and implementing practical changes and developing hope. The second domain, "Helpful and unhelpful treatment characteristics, " highlights treatment elements that either supported or hindered recovery: safety and containment; being cared for and respected; not being an equal partner in treatment; and focusing on change. The third domain, "The nature of change, " refers to clients' experience of change as an open-ended journey and a series of achievements and setbacks.Conclusions: The meta-synthesis highlights areas of change experienced by individuals receiving treatment for BPD, and treatment characteristics that they value. However, further research is needed to better understand how these changes are achieved.